ASSOCIATION OF OBESITY WITH RAPID VIROLOGICAL RESPONSE IN PATIENTS WITH CHRONIC HEPATITIS C - Haq, Moeen Ul; Hassan, Muhammad Kamran; Babar, Ahmad Nawaz; Khan, Aamir Ghafoor (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine the association of obesity with rapid virological response in patients with chronic hepatitis C on antiviral therapy. Methodology: In this prospective cohort study patients suffering from chronic hepatitis C who required treatment were included after getting ethical approval and informed consent. Patient's weight and height was measured and body mass index (BMI) was calculated. Patients were divided into 2 groups; group 1 having BMI <30 and group 2 having BMI >30 in equal numbers. All the patients were put on weekly pegylated interferon plus ribavirin in fixed divided doses. PCR was done at the completion of 4 week to check for rapid virological response (RVR). After completion of study these 2 groups were compared to see whether any significant association exists between BMI and RVR. RVR was also stratified among age, viral load and gender to see their effect as these are potential effect modifiers. Results: There were 140 (56.3 %) male and 110 (43.7%) female patients with male to female ratio of 1.2:1. Mean age of the patients was 39.78 ±9.85, while mean BMI was 27.40 ±5.86. Overall the RVR was achieved in 53.2% of the patients. Frequency of RVR was 77(61.6 %) in non-obese patients as compared to 56(44.8%) in obese patients with a p value of 0.008. Conclusion: Obesity is significantly associated with poor RVR in patients with chronic hepatitis C.